2022
DOI: 10.1371/journal.pgph.0000989
|View full text |Cite
|
Sign up to set email alerts
|

Analysing interventions designed to reduce tuberculosis-related stigma: A scoping review

Abstract: Stigma is a critical barrier for TB care delivery; yet data on stigma reduction interventions is limited. This review maps the available literature on TB stigma reduction interventions, using the Health Stigma and Discrimination framework and an implementation analysis to identify research gaps and inform intervention design. Using search terms for TB and stigma, we systematically searched PubMed, EMBASE and Web of Science. Two independent reviewers screened all abstracts, full-texts, extracted data, conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…While empowering PWTB through counselling can help them mitigate internal and anticipated stigma, interviews emphasized the parallel need to address discrimination and enacted stigma by health workers and community members. Our data support systematic and scoping review recommendations that suggest internal and anticipated stigma may be addressed effectively with interventions targeted at individuals using counselling or support groups, whereas enacted stigma may be better addressed with information-based interventions targeted at the organisational or community level ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 69%
“…While empowering PWTB through counselling can help them mitigate internal and anticipated stigma, interviews emphasized the parallel need to address discrimination and enacted stigma by health workers and community members. Our data support systematic and scoping review recommendations that suggest internal and anticipated stigma may be addressed effectively with interventions targeted at individuals using counselling or support groups, whereas enacted stigma may be better addressed with information-based interventions targeted at the organisational or community level ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 69%
“…In a recent systematic review we considered how stigma reduction interventions were implemented at each level of the socio-ecological model. 21 Existing interventions -all in the pilot stage -typically targeted one or possibly two levels; for example, TB support groups or clubs (individual/interpersonal), [40][41][42] home visits (individual/interpersonal), 42,43 education for patients/caregivers (individual/interpersonal), 44 health worker training (institutional), [45][46][47] and community-volunteer led education (community) 48 . This highlights a tension whereby, given limited resources, trade-offs are made between interventions at different levels of the socio-ecological model.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent scoping reviews on TB stigma interventions reported major gaps in existing literature, including inconsistent application of stigma de nitions, variable non-standardised measurement approaches, and incomplete reporting of intervention design and outcomes. 20,21 Furthermore, the quality of these studies was low, and no studies of psychological interventions measured stigma as a primary outcome. 20,21 Another review of interventions to address health-related stigma for diseases including TB and HIV highlighted that stigma interventions have hitherto focused on a single socio-ecological level (most often that of the individual), which limits their impact given that stigma drivers and experiences are pervasive across levels including individual, interpersonal, institutional, community, and policy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satunya dengan memberikan pengetahuan yang benar kepada masyarakat agar terjadi peningkatan pengetahuan terkait TB, sehingga mengurangi stigma pada kelompok masyarakat tertentu. Kemudian, intervensi yang diberikan kepada individu di rumah tangga atau lingkungan sosial yang terkena dampak dapat mengurangi stigma, seperti mengurangi rasa menyalahkan dan kesalahpahaman penyebab TB secara medis (Foster, Galloway, Human, Anthony, Myburgh, Vanqa, Wademan, Makanda, Tisile, Schoeman, Hoddinott, & Nathavitharana, 2022). Pendidikan kesehatan, seperti berbagi pengetahuan, kampanye tentang TB merupakan strategi efektif untuk mengurangi stigma TB.…”
Section: Pendahuluanunclassified